Голод 1932–1933 рр. у Білорусії: історіографічні парадокси, історична пам’ять та політика пам’яті - Гудзь, В.; Боряк, О. (Український історичний журнал, 2020)
Мета дослідження – проаналізувати, виявити особливості й узагальнити результати
досліджень білоруськими науковцями історії організованого голоду 1932–1933 рр. на територіях
радянських України та Білорусії. Методологія ґрунтується на принципах історизму, об’єктивності,
усебічності, системності. Для досягнення поставленої мети застосоване комплексне використання, крім загальнонаукових, спеціально-історичних методів: історіографічного, історико-ситуаційного, компаративного, усної історії. Наукова новизна. Стаття є першим спеціальним історіографічним дослідженням білоруських студій голоду 1932–1933 рр. на теренах Білорусії. Основні
результати й висновки. Відзначено, що історія голоду 1932–1933 рр. у Білорусії загалом замовчується в навчальному процесі, залишається на периферії білоруських академічних студій, проте
була активізована після прийняття Верховною Радою України закону про визнання Голодомору
геноцидом і реакції на це Російської Федерації. Виявлено вплив авторів російської концепції голоду 1932–1933 рр. як «спільної трагедії народів СРСР» зі співмірними наслідками, який виявився
у прирівнюванні білоруськими дослідниками причин голоду в БСРР до Голодомору в УСРР, перебільшенні людських втрат у республіці. Показано відмінність Голодомору як цілеспрямованого геноциду українського народу від голоду в Білорусії. На противагу деяким білоруським дослідникам стверджується, що голод у БСРР стався через надмірні заготівлі, непогоду, господарські помилки
в певних районах і завдав на порядок менших людських втрат, ніж в Україні. The goal of the research is to analyze, to reveal the peculiarities and to sum up the results
of study by Belarusian researchers of history of man-made famine of 1932–1933 on the territory of
Soviet Ukraine and Byelorussia. The methodology is based on principles of historicism, objectivism,
comprehenciveness and systematicness. To achieve set goals, intergrated use of other methods,
besides general schientific ones, was involved – special historical methods: historiography, historicalsituational,
comparative methods and “oral history” method. Research originality of the work.
The article is the first special historiographical research of Belarusian studies of the famine 1932–
1933 on the territory of Byelorussia. Main results and conclusions. History of the famine 1932–1933
in Byelorussia is generally suppressed in teaching process and is left on the periphery of Belarusian
academic studies. But it had been made more active after adoption by the Verkhovna Rada of Ukraine
of the law about confession of the Holodomor as genocide and reaction toward it of the Russian
Federation. The article has revealed influence of the authors of the Russian concept of the famine
1932–1933 as “collective tragedy of people of USSR” with commensurate consequences. The latter had
been shown in comparison of the reasons of the famine by the Belarusian researchers in Byelorussia
with the Holodomor in Ukraine, overestimation of human losses in the republic. The research shows
distinction of the Holodomor as the directed genocide against Ukrainian people from the famine in
Byelorussia. To the contrary of some Belarusian researchers, the authors claim that the famine in the
BSSR took place because of excessive grain procurements, poor weather, economic mistakes in some
raions and resulted into less human losses than in Ukraine.